Zasoby wiedzy w procesie zmian - Stańczyk-Hugiet, Ewa (Resources and capabilities in changes processes, 2005)
Presented paper concern on some potential activities in area of resources and capabilities depending on changes options especially strategic changes. Main interest is concern on Knowledge Resources as a primary resources. There are presented four models of changes: evolutionary, life cycle, dialectic and teleological. As a result it can be assumed that evolutionary and life cycle models don't guarantee important change in sense of quality. So, it can be assumed that important thing is dynamic point of view for changes processes (teleological and dialectical) rather than others and in consequences creative resources and capabilities shaping and also explorations processes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 160-166